A study on model-free approach for liquid slosh suppression based on stochastic approximation - Ahmad, Mohd Ashraf
Recently, with the rapid growth in science and engineering, most of the real world process plants have been built on a large scale and complex systems. As a consequence, modeling of such systems may become very difficult and require a lot of effort. Therefore, it is necessary to develop a control method that does not depend on plant models, which is known as the model-free control approach. At the same time, it is also worthy to consider an optimization tool for the model-free approach that is simple to understand for engineers and can optimize a large number of control parameters in a fast manner. So far, there have not been enough literatures to discuss the application of model-free control schemes for the above demands. Motivated by the above background, a model-free control scheme is considered in our study. Here, a Simultaneous Perturbation Stochastic Approximation (SPSA) algorithm is suggested as a promising tool for the model-free control approach. Then, this research report focuses on assessing the effectiveness of the SPSA-based algorithm for model-free proportional-integralderivative (PID) control tuning in liquid slosh problems. Slosh or oscillation of liquid inside a container often occurs in many cases, such as, vehicles or ships with liquid cargo carriers, molten metal industries, which is dangerous to handle by the operator. Moreover, sloshing of fuel and other liquids in moving vehicles may cause instability and rollover of the vehicle. For the past decades, various control strategies of liquid slosh motion are based on model-based control schemes. Nevertheless, these methods are difficult to apply in practice. The main reason is that their control schemes do not accurately consider the chaotic behaviour of slosh and the complex fluid dynamic motion in the container. Therefore, a model-free approach will be more attractive. In this research project, we propose a model-free PID controller design based on Simultaneous Perturbation Stochastic Approximation for controlling liquid slosh. The effectiveness of the proposed model-free PID based SPSA is evaluated in terms of liquid slosh reduction, tracking performance, and computation time. In addition, the performance of the SPSA based methods is compared to the other stochastic optimization based approaches, which also includes the variants of SPSA based method, such as Global SPSA. In this study, a real experimental rig of liquid slosh plant is considered to validate the effectiveness of our proposed scheme. In particular, we develop our own liquid slosh model from the input-output data of real plant through the system identification method. Then, the proposed model-free PID based SPSA is applied to the developed model. The outcome of this study has shown that the SPSA based methods, especially the GSPSA based method, are successfully produced better control performances as compared with other stochastic methods. In particular, the proposed modelfree PID scheme can produce slightly minimum liquid slosh motion while maintain the input tracking of the trolley position.